Teachers as Digital Facilitators: Navigating the Shift from Content Delivery to Learning Design - Afriani, Gusma; Sa'diyah, Sa'diyah; Krisnawati, Nova; Husnita, Liza; Komariah, Nur (Global Education Journal, 2025)
This study explores the evolving role of teachers as digital facilitators, focusing on the shift from traditional content delivery to learning design in digitally mediated classrooms. With the rapid integration of technology in education, many teachers still struggle to adapt their practices, which raises the question of how they can effectively transition to roles that require instructional design thinking and technological fluency. The research employs a qualitative methodology, utilizing semi-structured interviews, classroom observations, and document analysis to investigate the experiences of 12 secondary school teachers in West Java, Indonesia. The findings reveal that teachers are increasingly adopting roles as learning designers, curating digital tools and resources to foster student-centered, collaborative, and inquiry-based learning. However, challenges such as rigid curriculum standards, lack of institutional support, and limited professional development hinder the full realization of this shift. The study concludes that becoming an effective digital facilitator requires not only technical skills but also pedagogical flexibility, reflection, and systemic support.